ILMI: A Virtual Assistant for Learning Media in Accounting Inventory Courses - Yohan Bakhtiar; Abidatul Izzah; Dion Yanuarmawan; Fitria Nur Hamidah; Toga Aldila Cinderatama (Information Technology Education Journal, 2025)
Promoting interactive and engaging learning remains a major challenge, particularly in the design and development of instructional media that can serve as a virtual instructor for accounting students. To address this challenge, the present study introduces the development of a virtual teaching assistant specifically designed for accounting courses, with a focus on the inventory topic. The virtual assistant delivers guided instruction in audio format by utilizing Google’s text-to-speech technology, aiming to enhance students’ comprehension and engagement during learning activities and assessments. The integration of text-to-speech into inventory learning media represents the novelty of this research. Accordingly, the system named Interactive Learning Media of Inventory (ILMI) was developed through a structured process consisting of needs analysis, system design, implementation, user testing, and maintenance. Finally, the system was evaluated and achieved a SUS score of 79, indicating a high level of usability based on respondent feedback.